0.5(3x+6)=1.6-(x+2)

Simple and best practice solution for 0.5(3x+6)=1.6-(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(3x+6)=1.6-(x+2) equation:


Simplifying
0.5(3x + 6) = 1.6 + -1(x + 2)

Reorder the terms:
0.5(6 + 3x) = 1.6 + -1(x + 2)
(6 * 0.5 + 3x * 0.5) = 1.6 + -1(x + 2)
(3 + 1.5x) = 1.6 + -1(x + 2)

Reorder the terms:
3 + 1.5x = 1.6 + -1(2 + x)
3 + 1.5x = 1.6 + (2 * -1 + x * -1)
3 + 1.5x = 1.6 + (-2 + -1x)

Combine like terms: 1.6 + -2 = -0.4
3 + 1.5x = -0.4 + -1x

Solving
3 + 1.5x = -0.4 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + 1.5x + x = -0.4 + -1x + x

Combine like terms: 1.5x + x = 2.5x
3 + 2.5x = -0.4 + -1x + x

Combine like terms: -1x + x = 0
3 + 2.5x = -0.4 + 0
3 + 2.5x = -0.4

Add '-3' to each side of the equation.
3 + -3 + 2.5x = -0.4 + -3

Combine like terms: 3 + -3 = 0
0 + 2.5x = -0.4 + -3
2.5x = -0.4 + -3

Combine like terms: -0.4 + -3 = -3.4
2.5x = -3.4

Divide each side by '2.5'.
x = -1.36

Simplifying
x = -1.36

See similar equations:

| -3(x-4)-2(x+3)=-5x+6 | | 100-z=65 | | 5,6x=1,176 | | 6x-6=15x-5 | | lnx+ln(2x+1)=4 | | 0.6(4x+8)=1.6-(x+2) | | 10x+2=2x+30 | | -3x^2+9x=1 | | (X-11)(7x-1)=0 | | -3(x-4)-2(x+3)=-5(-1) | | 2t+2=9 | | 6(x+1)/5=3x-1 | | -12=p-7 | | x+y=27 | | 6x-12+4x+2=90 | | 0.6(7x+14)=1.4-(x+2) | | x=22-x | | 9x-5=29 | | 9x+5=86 | | ln(x+5)-ln(x-4)=3 | | .5x+.05(170)=.25(70) | | 10x-2=x+25 | | (3/10)x-(2/5)=-1 | | 5-2=3 | | (3/4)x+(5/4)=-(7/4) | | y^2-3y-12=0 | | -4y-23=6y+17 | | 5x+4=-4+3x+14 | | 4(3x+7)=64 | | 2m+5=4m-4 | | r-3/10=r/16 | | -6(x-5)+3=33 |

Equations solver categories